Maintenance of stem cell activity in plant development and stress responses - Zhang, Huankai; Mu, Yangwei; Zhang, Hui; Yu, Caiyu (Frontiers in Plant Science, 2023)
Stem cells residing in plant apical meristems play an important role during postembryonic development. These stem cells are the wellspring from which tissues and organs of the plant emerge. The shoot apical meristem (SAM) governs the aboveground portions of a plant, while the root apical meristem (RAM) orchestrates the subterranean root system. In their sessile existence, plants are inextricably bound to their environment and must adapt to various abiotic stresses, including osmotic stress, drought, temperature fluctuations, salinity, ultraviolet radiation, and exposure to heavy metal ions. These environmental challenges exert profound effects on stem cells, potentially causing severe DNA damage and disrupting the equilibrium of reactive oxygen species (ROS) and Ca 2+ signaling in these vital cells, jeopardizing their integrity and survival. In response to these challenges, plants have evolved mechanisms to ensure the preservation, restoration, and adaptation of the meristematic stem cell niche. This enduring response allows plants to thrive in their habitats over extended periods. Here, we presented a comprehensive overview of the cellular and molecular intricacies surrounding the initiation and maintenance of the meristematic stem cell niche. We also delved into the mechanisms employed by stem cells to withstand and respond to abiotic stressors.